Rafflesia tuanku-halimii (Rafflesiaceae), a new species from Peninsular Malaysia - Jumaat Haji Adam,; Mohd Afiq Aizat Juhari,; Rahmah Mohamed,; Nor Azilah Abdul Wahab,; Syamsurina Arshad,; Mohd Paiz Kamaruzaman,; Mohd Firdaus Mohd Raih,; Wan, Kiew-Lian (Penerbit Universiti Kebangsaan Malaysia, 2016)
Rafflesia tuanku-halimii, a new species from Peninsular Malaysia, is herewith described and illustrated. It is related to R. azlanii and R. sharifah-hapsahiae by coalesced warts on it lobes. Rafflesia tuanku-halimii is different from them in having window covered by almost united rings and these rings almost wholly covering the window.